Participation of the 39-kDa glycoprotein (gp39) of the vitelline envelope of Bufo arenarum eggs in sperm-egg interaction - Barrera, Antonio Daniel (2012)
The acquisition of egg fertilizability in Bufo arenarum takes place during the oviductal transit and during this process the extracellular coelomic envelope (CE) of the eggs is converted into the vitelline envelope (VE). It has been stated that one of the necessary events leading to a fertilizable state is the proteolytic cleavage of CE glycoproteins in the oviductal pars recta by oviductin, a serine protease. Consequently, there is a marked increase in the relative quantity of glycoproteins with 39 (gp39) and 42-kDa (gp42) in the VE. In the present study, sperm-VE binding assays using heat-solubilized biotin-conjugated VE glycoproteins revealed that both gp39 and gp42 have sperm binding capacity. According to this result, our study was focused on gp39, a glycoprotein that we have previously reported as a homologue of mammalian ZPC. For this purpose, rabbit polyclonal antibodies against gp39 were generated at our laboratory. The specificity of the antibodies was confirmed with Western blot of VE glycoproteins separated on SDS-PAGE. Immunohistochemical and immunoelectron studies showed gp39 distributed throughout the width of the VE. In addition, immunofluorescence assays probed that gp39 bound to the sperm head. Finally, as an approach to elucidate the possible involvement of gp39 in fertilization, inhibition assays showed that pretreatment of eggs with antibodies against gp39 generated a significant decrease in the fertilization rate. Therefore, our findings suggest that gp39, which is modified by oviductal action, participates as a VE glycoprotein ligand for sperm in Bufo arenarum fertilization.